2002
DOI: 10.1007/s00221-001-0934-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between different sensory cues in the control of human gait

Abstract: This experiment investigates the interaction of different sensory cues in the control of propulsive forces in human gait which in turn allow the body's forward progression to be regulated. The aim of this work was to determine how optic flow and leg-somatosensory feedback interact in this control. We therefore determined whether the responses to sinusoidal perturbations of optic flow were accentuated when leg-somatosensory feedback was modified by varying the support resistance. Subjects walked on a treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 17 publications
8
44
1
Order By: Relevance
“…Results of the present study demonstrate that walking speed is modulated out-of-phase with OF speed in healthy subjects, which is consistent with previous studies [6][7][8], despite the fact that expanding OFs were simulated by a meaningful and rich virtual environment in the present study. Previous research used gratings composed of dots, spots or diamonds oscillating to form contracting and expanding OFs [6][7][8].…”
Section: Mean Cross-correlation Coefficients (A) and Phase Lags (B)supporting
confidence: 93%
See 2 more Smart Citations
“…Results of the present study demonstrate that walking speed is modulated out-of-phase with OF speed in healthy subjects, which is consistent with previous studies [6][7][8], despite the fact that expanding OFs were simulated by a meaningful and rich virtual environment in the present study. Previous research used gratings composed of dots, spots or diamonds oscillating to form contracting and expanding OFs [6][7][8].…”
Section: Mean Cross-correlation Coefficients (A) and Phase Lags (B)supporting
confidence: 93%
“…Previous research used gratings composed of dots, spots or diamonds oscillating to form contracting and expanding OFs [6][7][8]. The observed non-volitional changes in gait speed induced by changes in OF speed in our healthy age-matched controls, although consistent, were of small magnitude.…”
Section: Mean Cross-correlation Coefficients (A) and Phase Lags (B)supporting
confidence: 59%
See 1 more Smart Citation
“…The results confirmed that motor correction always preceded conscious awareness of a mismatch. Varraine et al (2002) demonstrated partly analogue results for treadmill walking. In this experiment participants unconsciously adjusted their walking characteristics, force or speed, for about 6 s even though they were explicitly asked to report these changes as soon as they arose (although this delayed awareness may result from a difference in the paradigm as perturbations were only increased gradually and no visual feedback was available to the participants).…”
Section: Movement Correction and Agencymentioning
confidence: 84%
“…Evidence continues to accumulate that the vestibular apparatus functions as an inertial navigational system (Berthoz and Pozzo, 1994;Dunbar et al, 2004;Mayne, 1974;Pozzo et al, 1990) within the stable platform of the head (Pozzo et al, 1990), and is sensitive to the gravito-inertial acceleration vector (Imai et al, 2001). Together, these visual and vestibular cues can also determine locomotor velocity (speed of approach) and acceleration (Bertin et al, 2000;Prokop et al, 1997;Telford et al, 1995;Varraine et al, 2002). During walks, by contrast, a stabilized trunk can provide information about spatial orientation by combining signals from the vestibular apparatus and neck proprioceptors (Mergner et al, 1983(Mergner et al, , 1991(Mergner et al, , 1992, and from proprioceptors (Jacobs et al, 1985;Mittelstaedt, 1988;Taylor and McCloskey, 1990) and nonproprioceptive receptors (Mittelstaedt, 1995(Mittelstaedt, , 1996(Mittelstaedt, , 1997Vaitl et al, 1997) in the trunk itself.…”
mentioning
confidence: 99%